Sleeping disorders in older adults. Diagnostic and therapeutic update - Ivette Cepero Pérez; Miriam González García; Odalys González García; Thaimi Conde Cueto (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Sleeping disorders in the elderly are a frequent condition. However, it is a part of relatively new medicine, since it has only been in the last 40 years it has really studied. The objective of this review is to deepen and update diagnostic and therapeutic aspects of these disorders, which is always a challenge for the doctor who attends this age group.